Rancang Bangun Sistem Pendeteksi Tsunami (Studi Kasus Selat Sunda) - Saputro, Agung; Triarmadja, Radianta; Priyosulistyo, Henricus (Universitas Negeri Yogyakarta, 2022)
Tsunami is not only caused by the strength of tectonic earthquakes with the dislocation of the seafloor, but also by landslides /rocks in shallow waters, or the relatively large fall of meteors/ celestial bodies. Unlike other tsunamis caused by slab collisions, tsunamis in the Sunda Strait tsunami caused by high tides and underwater landslides due to the eruption of krakatoa. Tsunami due to the eruption of Mount Anak Krakatau threatens at any time so that technology is needed to be able to help the community and BMKG monitor activities in the Sunda Strait so as to provide security and comfort of the surrounding residents. Therefore, research was made to measure the height of waves to detect high waves causing tsunamis in the Sunda Strait. In this research, Tsunami detection system using electrical circuits in its testing with submersible sensors as a wave height reader. The result of the sensor height readings read by the sensor in the process uses a Resberry-Pi microcontroller. The height limit set on the sensor produces siren sounds and sends short messages sent to residents of coastal communities of the Sunda Strait. The results showed that the tsunami detection system managed to read the water level in real time accurately according to the calibration equation. The water level reading tool set by the limit is 2 meters with the length of the wave using a maximum time of 90 seconds. The device will send a short message and produce a siren sound when the wave reaches a height of 2 meters for 90 seconds in a row. Sending messages takes 2-5 seconds, if there is a tsunami due to the eruption of Mount Anak Krakatau the evacuation time to the safe zone for coastal communities of the Sunda Strait is still affordable and safe.